Material selection using hybrid MCDM approach for automobile bumper. (1st January 2013) - Ilangkumaran, M.; Avenash, A.; Balakrishnan, V.; Kumar, S. Barath; Raja, M. Boopathi
This paper describes an application of multi-criteria decision-making (MCDM) techniques to evaluate optimum material to be employed for manufacturing of automobile bumper. The proposed hybrid MCDM technique involves fuzzy analytical hierarchy process (FAHP) integrated with preference ranking organisation method for enrichment evaluation (PROMETHEE). FAHP is used to compute the criteria weights. PROMETHEE I is used to find out the leaving and entering flows, whereas PROMETHEE II is used to find the total ranking of the material. This study focuses on five alternatives such as polyethylene, polypropylene, acrylonitrile butadiene styrene, polyamide and polystyrene. This study uses six evaluation criteria such as compressive yield strength, flexural modulus, hardness, Charpy impact strength, elongation and cost to select the appropriate material.